2021
DOI: 10.3389/fcvm.2021.705169
|View full text |Cite
|
Sign up to set email alerts
|

Social Jetlag and Cardiometabolic Risk in Preadolescent Children

Abstract: Objective: Childhood cardiometabolic disease risk (CMD) has been associated with short sleep duration. Its relationship with other aspects of sleep should also be considered, including social jetlag (SJL) which represents the difference between a person's social rhythms and circadian clock. This study investigated whether childhood CMD risk is associated with sleep duration, sleep disturbances, and SJL.Study Design: The observational study included 332 children aged 8–10 years (48.5% female). The three indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…In other words, our statistical approach was more sensitive to this effect and picked up this association in girls either because they are more prone to this relation as hypothesized ( 8 , 18 , 41 , 43 45 ) or because our sample had more girls. This corroborates findings that components of cardiometabolic risk and adverse endocrine profiles other than adiposity are associated to SJL in pediatric populations ( 27 ) and other sleep disturbances (e.g., short sleep duration and bad quality sleep ( 31 34 ). The reason for this higher sensitivity of a latent factor is due to the fact that a cardiometabolic latent factor represents the shared variance of different continuous parameters that express an underlying theoretical cardiometabolic construct and partials out the specific effects of individual indicators ( 46 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In other words, our statistical approach was more sensitive to this effect and picked up this association in girls either because they are more prone to this relation as hypothesized ( 8 , 18 , 41 , 43 45 ) or because our sample had more girls. This corroborates findings that components of cardiometabolic risk and adverse endocrine profiles other than adiposity are associated to SJL in pediatric populations ( 27 ) and other sleep disturbances (e.g., short sleep duration and bad quality sleep ( 31 34 ). The reason for this higher sensitivity of a latent factor is due to the fact that a cardiometabolic latent factor represents the shared variance of different continuous parameters that express an underlying theoretical cardiometabolic construct and partials out the specific effects of individual indicators ( 46 ).…”
Section: Discussionsupporting
confidence: 89%
“…The reason for this higher sensitivity of a latent factor is due to the fact that a cardiometabolic latent factor represents the shared variance of different continuous parameters that express an underlying theoretical cardiometabolic construct and partials out the specific effects of individual indicators ( 46 ). This makes this analytic approach advantageous to assess its association with SJL compared to: 1) averaging across ( 21 , 35 ) or combining various indicators in multivariate analyses ( 27 ); 2) using a metabolic syndrome index ( 28 , 30 , 31 , 34 ), for which there is no consensus in terms of which indicators should be used ( 49 ), their cutoff scores or for which adjustments (e.g., for age, sex and pubertal status) should be made ( 51 54 ); and 3) using multiple analyses, one for each cardiometabolic-related variables, which still seems to be the norm in the sleep literature. In point of fact, our post hoc exploratory correlations of SJL with each cardiometabolic indicator did not survive corrections for multiple comparison in either sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous publication on a different dataset of adult participants from two Czech townships revealed that HDL is significantly lower in both extreme early and late age- and sex-normalized MSF sasc chronotypes [ 40 ], a result that we have now confirmed using this independent, larger, and more representative dataset ( Figure 2F , Kruskal–Wallis, p < 0.0001). Moreover, AIP, a cardiovascular disease risk predictor [ 47 ], was significantly increased in both extreme MSF sasc chronotypes ( Figure 2G , Kruskal–Wallis, p = 0.0001). To explore further, we calculated mixed effects models where instead of chronotype we included the spread from the median of chronotypes (median absolute deviation, MAD_MSF sasc , see methods) as the explanatory variable.…”
Section: Resultsmentioning
confidence: 99%
“…Since BMI is in our dataset positively associated both with total cholesterol ( Table 1 ) as well as with social jetlag, and obesity, in general, is a factor previously reported to be linked with higher social jetlag [ 25 , 26 ], it is not surprising to find higher cholesterol levels in participants with higher social jetlag. Indeed, several studies have reported association of social jetlag with cholesterol in different cohorts including preadolescent children [ 47 ], midlife adults [ 31 ], and patients with hypertension or diabetes [ 37 , 48 ]. In contrast, a similarly sized study on an older (>50 y) population [ 28 ] did not detect any significant association between social jetlag and cholesterol or triglycerides, but reported association of social jetlag with higher glucose levels.…”
Section: Discussionmentioning
confidence: 99%